Comparative analysis of humus balance under grain crops and perennial bean cultures of a farmland - A. D. Gumbarov; E. V. Dolobeshkin (Новые технологии)
The reduction of humus reserves, as one of the components of soil fertility, is influenced by the shortage of soil biomass on lands in agricultural use. The accumulation of humus reserves in the agrolandscape is a multifactorial process. In the article, the authors examined the "humus balance" as a factor influencing the total humus reserves in the soil. The method of calculating the balance of humus is based on the content of nitrogen in the humus. A comparative analysis of the processed research data in the SEC Kolkhoz «Memory of Lenin» in the Timashevsky district of the Krasnodar Territory shows that the proportion and yield of crops affect the balance of humus. So for grain (humus-consuming) crops, an increase in yield leads to an increase in the negative balance of humus under the crop: +(Y) = + (-ΔГ). The opposite situation under perennial leguminous (humus-forming) crops: +(Y) = +(ΔГ). In addition, a large proportion of grain (profitable) crops in the composition of arable land mainly negatively affects the average weighted humus balance of arable land. Thus, a small proportion of perennial crops does not allow for overlapping the negative dynamics of the humus balance of arable land. An increase in the share of perennial legumes, with a stable yield, would play an important role in restoring and stabilizing arable land humus reserves.